Genetic Polymorphisms Associated with Obesity in Southeast Asian Populations: A Systematic Review without Meta-Analysis - Vijakumaran, Ubashini; Abdul Murad, Nor Azian; Abdul Jalal, Muhammad Irfan; Chin, Siok Fong; A Jamal, A Rahman; Abdullah, Noraidatulakma (Malaysian Journal of Medical Sciences, 2025)
Obesity is a growing global public health challenge, with genetic factors playing a crucial role in its development. This review synthesises findings from Southeast Asian studies to investigate the association between gene polymorphisms and obesity risk across various ethnic populations. A comprehensive search of three databases, PubMed, Scopus, and Web of Science, initially retrieved 2,021 articles, from which 25 studies were meticulously selected based on stringent inclusion and exclusion criteria. The quality of the studies was assessed through the Newcastle-Ottawa Scale (NOS), a risk bias tool. These studies encompass 8,312 participants and examined 33 single nucleotide polymorphisms (SNPs). UCP polymorphism demonstrated a significant association with overall adiposity (OR = 2.02, P = 0.01) in Malaysian women, while the rs659366 UCP2 was linked to weight gain in an Indonesian cohort. LEP variants were not significantly associated with obesity in Malaysians, and FTO variants showed mixed results, with rs9939609 (OR = 3.72, P = 0.009) and rs1421085 (OR = 3.22, P < 0.001) variants being associated with obesity and higher body mass index (BMI) in Indonesians, but no significant findings in Malaysians. These results emphasise the genetic diversity within Southeast Asia and the challenges in replicating genetic associations across populations. To address these inconsistencies and improve our understanding of obesity in Southeast Asia, there is a pressing need for more extensive and diverse cohort studies, complemented by comprehensive genome-wide association studies (GWAS), to identify robust obesity biomarkers in Southeast Asia.